ICT Sector Performance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
These studies are the first contribution by network members to the realisation of the RIA! vision – our vision of a biquitous African information society and knowledge economy, actively shared in by all.